2011
DOI: 10.1021/pr200331k
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Labeling of Chondrocytes for the Quantitative Analysis of the Interleukin-1-beta-mediated Modulation of Their Intracellular and Extracellular Proteomes

Abstract: Chondrocytes are widely used as an in vitro model of cartilage diseases such as osteoarthritis (OA). As the unique residents of mature cartilage, they are responsible of the synthesis and release of proteins essential for a proper tissue turnover. In this work, the stable isotope labeling with amino acids in cell culture (SILAC) technique has been standardized in primary human articular chondrocytes (HACs) for quantitative proteomic analyses. Then, it has been employed to study those protein modifications caus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
54
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 36 publications
(57 citation statements)
references
References 38 publications
3
54
0
Order By: Relevance
“…Calamia et al also reported vimentin was the most abundant protein expressed after cytokine treatment to chondrocytes. 52 Interestingly in microarray results, vimentin was 5.8-fold upregulated in the in vitro OA model compared to the OA cartilage biopsies, whereas it was 59.98-fold upregulated in the in vitro OA model compared to tissue-engineered cartilage (Fig. 8D).…”
Section: Tissue-engineered Model Of Osteoarthritismentioning
confidence: 88%
“…Calamia et al also reported vimentin was the most abundant protein expressed after cytokine treatment to chondrocytes. 52 Interestingly in microarray results, vimentin was 5.8-fold upregulated in the in vitro OA model compared to the OA cartilage biopsies, whereas it was 59.98-fold upregulated in the in vitro OA model compared to tissue-engineered cartilage (Fig. 8D).…”
Section: Tissue-engineered Model Of Osteoarthritismentioning
confidence: 88%
“…Nevertheless, two-dimensional gels present a number of limitations, such as the difficulties in focusing very acidic proteins (greatly represented in cartilage by the high density and anionic nature of proteoglycans). To avoid these problems and to increase the dynamic range for a more accurate protein quantification (usually, 1-2 orders of magnitude in two-dimensional electrophoresis experiments), we recently developed an alternative method based on SILAC for the quantitative analysis of chondrocytes proteome and secretome (15). The present work illustrates the successful complement of the best quantitative gel-based method up to date (DIGE) for the proteomic analysis of intracellular proteins and the SILAC approach followed by LC-MS analysis for the quantitative study of extracellular proteins.…”
Section: Discussionmentioning
confidence: 99%
“…In the case of light media, standard L-lysine and L-arginine were added, whereas in the heavy media, isotope-labeled L-lysine ( 13 C 6 ) and isotope-labeled L-arginine ( 13 C 6 , 15 N 4 ) were used. Cell expansion was carried out as described previously by our group (15). Chondrocytes were used at week 3 in primary culture (P1) when 100% of labeling was reached.…”
Section: Methodsmentioning
confidence: 99%
“…In the case of light media, standard L-lysine and L-arginine were used, while in the heavy media isotope-labelled L-lysine ( 13 C 6 ), and isotope-labeled L-arginine ( 13 C 6 , 15 N 4 ) were added at 146 mg/L for K and 28 mg/L for R. HACs expansion, cell type verification by the assessment of COL2 expression, and evaluation of complete labeling were performed as described previously by our group [24]. Cell proliferation and cell viability were tested by cell count and Trypan Blue dye exclusion.…”
Section: Silac Of Primary Cultured Hacsmentioning
confidence: 99%
“…Then, heavy and light samples were mixed 1:1, and 6 g of each mixed sample were separated onto a 10% SDS-PAGE gel. Gels were stained with Coomassie blue and the resulting lanes were cut into six slices and subjected to in-gel digestion according to previous protocols [24]. Digestion was performed overnight with 12.5 ng/L of Sequencing Grade Modified Trypsin (Promega) at 37ЊC.…”
Section: Collection and Preparation Of Conditioned Media For Analysismentioning
confidence: 99%